Workplace Violence: Consequences and Solutions in Healthcare Institutions - Shaikh, Khalil Ahmed; Nisar, Nusrat; Bukhari, Dua; Fatima, Muqadas; Ali Shah, Syed Zulfiqar; Jahanghir, Syed; Qadeer, Farheen (Pakistan Journal of Medical & Health Sciences, 2024)
Violence may appear in a variety of contexts, such as private homes, public places, commercial spaces, colleges and universities, and other facilities1. It has a profound effect on people from all social classes. Because there was no standard term for violence, which made it a complicated and pervasive issue, it was not previously seen as a public health concern2. There is more to understanding violence than just tying it to empirical data. Instead, it entails making decisions about what constitutes proper and acceptable behaviour, which are influenced by societal norms, beliefs, and practices3. The deliberate use of force, real or threatened, towards themselves, another individual, an organisation or society, or oneself is what the World Health Organization, or WHO, defines as violence. This conduct has the risk of causing injury, death, psychological suffering, stunted growth, or impoverishment4. Although professional violence, including punching, kicking, shoving, hitting, shooting, and harming, has been acknowledged, until recently, little has been done to combat intellectual assault5. The intentional use of harm towards a person or group, including the threat or application of blunt force, is referred to as psychological abuse. The victim of this kind of assault may have detrimental effects on their psychological, ethical, moral, physical, and cognitive well-being6.